Reactivation of organophosphate-inhibited acetylcholinesterase by quaternary pyridinium aldoximes - Kuca, Kamil; Patocka, Jirí; Cabal, Jirí; Jun, Daniel (Neurotoxicity research, 2004)
We investigated the relationship between the chemical structure of acetylcholinesterase (AChE; EC 3.1.1.7) reactivators and their potency in reactivating this enzyme, after prior inhibition by VX (O-ethyl-S-(2-diisopropylaminoethyl)-methylthiophosphonate), tabun, sarin, and cyclosarin. The oximes, pralidoxime (2-PAM), HI-6 [1-(2-hydroxyiminomethylpyridinium)-3-(4-carbamoylpyridinium)-2-oxa-propane dichloride], obidoxime and HS-6 [1-(2-hydroxyiminomethylpyridinium)-3-(3-carbamoylpyridinium)-2-oxa-propane dichloride] were used as representatives of the group of AChE reactivators. Rat brain AChE was used as the appropriate source of the enzyme. Our results confirm that there is no single broad-spectrum oxime suitable for the treatment of poisoning with all highly toxic organophosphorus agents.
Keywords: Dose-Response Relationship, Drug; pyridinové sloučeniny; Rats; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; Cholinesterase Inhibitors; mozek; Oximes; krysa rodu Rattus; Pyridinium Compounds; organofosfáty; Enzyme Activation; Brain; zvířata; aktivace enzymů; Organophosphates; oximy; reaktivátory cholinesterasy; Animals